LNG energy transfer uncertainty–sensitivity to composition and temperature changes. (August 2015) - Graham, Emmelyn; Kenbar, Asaad
Abstract: Determining and reducing the measurement uncertainty of LNG energy transfer in custody transfer operations is considered extremely important and challenging for industry. The European Metrology Research Programme (EMRP) for Liquefied Natural Gas (LNG) has been focused on reducing the uncertainty in the evaluation of LNG energy transfers by improving existing measurement methods, validating new measurement methods and development of new traceable calibration systems. Part of this project was to produce realistic measurement uncertainty budgets and to determine the sensitivity of the overall LNG energy transfer uncertainty to changes in the composition and temperature of different LNG cargoes. This paper provides details on the development of an uncertainty budget and the results from the sensitivity study. It was found that the uncertainty in the LNG energy transfer ranged from 0.56% to 0.77% when using the uncertainty budget for 461 LNG cargoes. The variation was mainly due to the difference in the LNG composition and its associated uncertainty.